Identifying students’ mental models of sound propagation: the role of conceptual blending in understanding conceptual change - Hrepic, Zdeslav; Zollman, Dean A.; Rebello, N. Sanjay (My University, 2012)
We investigated introductory physics students’ mental models of sound propagation. We used a phenomenographic method to analyze the data in the study. In addition to the scientifically accepted Wave model, students used the “Entity” model to describe the propagation of sound. In this latter model sound is a self-standing entity, different from the medium through which it propagates. All other observed alternative models contain elements of both Entity and Wave models, but at the same time are distinct from each of the constituent models. We called these models “hybrid” or “blend” models. We discuss how students use these models in various contexts before and after instruction and how our findings contribute to the understanding of conceptual change. Implications of our findings for teaching are summarized.
Keywords: Mental models; Sound propagation; Conceptual blending; Conceptual change